2016
DOI: 10.11621/pir.2016.0403
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological methods for the diagnostics of human functional states: New approaches and perspectives

Abstract: in his famous methodological essay "The historical meaning of psychological crisis" (1928) emphasized the importance of studying any psychological process or state as a "whole"-that is, as characterized from the subjective and objective sides at the same time. This position is fully relevant for studying the human functional states (FSes). Today the objective psychophysiological diagnostics of human FSes in activities associated with a high risk of technological disasters (in nuclear-power plants, transportati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…These results confirmed that higher anxiety levels may be associated with the increase in the forehead temperature, as suggested by previous works [ 29 , 30 , 31 , 32 ]. Since the forehead area is one of the most stable temperature regions due to central vessel irrigation, thermal variations in this area are of great importance to provide information about stress diagnosis [ 30 , 33 ]. Likewise, maximum and average temperature values were positively correlated with the anxiety traits prior to the simulation practice [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results confirmed that higher anxiety levels may be associated with the increase in the forehead temperature, as suggested by previous works [ 29 , 30 , 31 , 32 ]. Since the forehead area is one of the most stable temperature regions due to central vessel irrigation, thermal variations in this area are of great importance to provide information about stress diagnosis [ 30 , 33 ]. Likewise, maximum and average temperature values were positively correlated with the anxiety traits prior to the simulation practice [ 22 ].…”
Section: Discussionsupporting
confidence: 92%